Longstanding refractory pseudophakic cystoid macular edema resolved using intravitreal 0.7 mg dexamethasone implants - Brynskov T (Dove Medical Press, 2013)
Troels Brynskov,1,2 Caroline Schmidt Laugesen,1 Jakob Halborg,1 Henrik Kemp,1 Torben Lykke Sørensen1,21Department of Ophthalmology, Copenhagen University Hospital Roskilde, Roskilde, Denmark; 2Faculty of Health Sciences, University of Copenhagen, Copenhagen, DenmarkBackground: Refractory pseudophakic cystoid macular edema (PCME) following cataract surgery has long posed a challenge to clinicians, but intravitreal injections with a sustained delivery 0.7 mg dexamethasone implant has emerged as a promising therapy for this condition.Objective: To present a case of longstanding and refractory PCME with complete remission through 189 days of follow-up after two successive injections with intravitreal dexamethasone implants.Case report: A 59-year-old male had experienced metamorphopsia for approximately 4 years and had been diagnosed with PCME 15 months earlier. Since the time of the diagnosis, the condition had been refractory to both subtenon triamcinolone acetonide and a total of five injections with intravitreal ranibizumab. After the last injection with ranibizumab, central subfield mean thickness was 640 µm, and the best corrected visual acuity was 78 Early Treatment Diabetic Retinopathy Study letters. Following an intravitreal injection with a dexamethasone implant, the macular edema resolved at the next follow-up. The macular edema returned 187 days after the first injection and was treated with another intravitreal dexamethasone implant. Again, the macular edema subsided completely, and best corrected visual acuity improved to 84 Early Treatment Diabetic Retinopathy Study letters, a condition which was maintained through an additional 189 days of follow-up.Conclusion: Chronic PCME is traditionally a difficult condition to treat, but we are encouraged by the optimal response experienced with intravitreal sustained release dexamethasone implants in our patient whose longstanding PCME had been refractory to previous treatments with both subtenon triamcinolone and intravitreal ranibizumab. In this case, the condition appeared to be fully reversible once inflammation was controlled, but the need for monitoring and repeated injections remains an issue of concern.Keywords: intravitreal dexamethasone implant, pseudophakic cystoid macular edema, Ozurdex®, Irvine-Gass syndrome